Diversity and heterogeneity of smallholder vegetable farming systems and their impact on food security and income in Malawi - Nzima, Wisdom Madede; Ip, Ryan H. L.; Bhatti, Muhammad Azher; Godfrey, Sosheel Solomon; Eik, Lars Olav; Gondwe, Sera Rose; Divon, Shai André (Frontiers in Sustainable Food Systems, 2024)
Household food security and income play central roles in sustainable development at the global, national, and local levels. Smallholder vegetable farming systems are widely regarded as crucial contributors to enhancing household food security and income in the developing world. Comprehensive whole-farm analysis of smallholder vegetable farming systems points out greater diversity and heterogeneity driven by interactions of socioeconomic and biophysical factors such as land profiles, land use, farm assets, enterprise income, off/non-farm activities, and household structure and expenditure. However, three distinct farm typologies exist (Resource and Livelihood Constrained Off-farm Dependent/Supplemented–RLCOD farmers, Resource and Livelihood Abundant and Commercial Oriented–RLACO farmers, and Medium Resources and Livelihoods Constrained Market Oriented–MRLCMO farmers), exhibiting significant differences and variability in structural and functional factors. The production of maize, groundnuts, soybean, and bean crops remains the primary source of livelihood for all farm typologies. Similarly, vegetable production is vital for farmers’ livelihoods in all farm types, yielding more income than food needs. However, both crop and vegetable productivity and production are still low and below the national and potential target across farm typologies. Small-scale irrigation offers one alternative solution in the context of increasing climate change. Small livestock (chickens, goats, and pigs) play a significant role in the livelihood of vegetable farmers despite their low productivity. Disparities exist across farm typologies in available arable and irrigable land, available household labor, capacity to hire additional labor, farm assets, and inputs, as well as participation in off-farm and non-labor-farm activities. While vegetable production and its proportion sold and earned income emerge as critical factors affecting household food accessibility and acquisition, additional factors such as crop production, proportion of crops sold, daily food expenditure, livestock income, and TLU significantly influence household access for different farm typologies, requiring consideration to achieve food security in vegetable farming systems.